Improving Expression of Pepsinogen A from Homo sapiens in Aspergillus niger by Using a Multi-Copy Gene Knock-in Strategy - Jie Chen; Ling Gui; Boyu Chen; Yuang Sun; Yongcan Zhao; Fuping Lu; Ming Li (Fermentation, 2023)
Pepsinogen A (PGA) plays an important role in the treatment of human gastrointestinal diseases. At present, PGA is mainly extracted from pig stomach, so its source is very limited and its price is very expensive. Production of PGA by microbial fermentation using an engineered strain with high PGA yield would be an ideal solution. This paper presents a new system for the high-level expression of PGA from Homo sapiens (hPGA) in Aspergillus niger. The hPGA5 gene codon was optimized according to the codon bias of A. niger and then connected to a strong promoter and signal peptide to construct an hPGA5 expression cassette. An ingenious multi-copy knock-in expression strategy mediated by the CRISPR/Cas9 tool was used to improve the production of hPGA in A. niger. By optimizing the copy number and integration sites of the hPGA5 gene, an engineering strain with a high yield of hPGA was constructed. After shake-flask fermentation for 7 d, the enzyme activity of recombinant hPGA reached 542.3 U/mL, which is the highest known activity. This lays a foundation for the production of hPGA by microbial fermentation.